Highly efficient, coking-resistant SOFCs for energy conversion using biogas fuels12. Issue 37 (7th October 2015) - Ma, Jianjun; Jiang, Cairong; Connor, Paul A.; Cassidy, Mark; Irvine, John T. S.
<x xml:space="preserve">Abstract</x> A well-designed cell structure and selected components makes it possible to obtain excellent performance combined good durability using biogas fuel.